Exploring Madurese Ethnoscience through the Preservation of the Ondhâgghâ Bhâsa Language in Community Texts: A Source of Contextual Science Learning - Moh. Amrullah Stani; Hodairiyah; Suhartatik (Jurnal Penelitian Pendidikan IPA, 2026)
This study explores Madurese ethnoscience as embedded in community texts written in Ondhâgghâ Bhâsa—the formal register of the Madurese language—and examines how efforts to preserve this linguistic form serve as a foundation for contextual science learning. Focusing on the Tonggalate Reading House community in Giligenting Subdistrict, Sumenep Regency, the research adopts a qualitative descriptive approach informed by sociolinguistics and ethnoscience perspectives. Data were collected through observation, in-depth interviews with community members and educators, and thematic analysis of locally produced texts that integrate traditional knowledge, ecological practices, and cultural values. The findings indicate that Ondhâgghâ Bhâsa functions not only as a vehicle for cultural identity but also as a medium through which indigenous scientific understandings—such as local environmental management, agricultural techniques, and medicinal practices—are documented and transmitted. These community texts thus provide authentic, culturally grounded resources for science education. The study concludes that preserving Ondhâgghâ Bhâsa through community literacy initiatives simultaneously safeguards Madurese ethnoscience and offers meaningful contexts for developing relevant, student-centered science learning experiences.